High-strength degradable polypropylene composite material as well as preparation method and application thereof

A biodegradable polypropylene composite with coffee grounds and PHA, enhanced by a silicon coupling agent, addresses flexibility and interfacial issues, achieving high strength and controlled degradation for improved 3D printing and environmental sustainability.

CN120310146APending Publication Date: 2025-07-15天津大学浙江研究院 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510575414.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Traditional polypropylene materials have shortcomings in toughness, biodegradability and 3D printing performance, especially in low temperature environments, are prone to brittle cracking, non-degradable, and have a high shrinkage rate of 3D printing, making it difficult to meet the needs of complex working conditions and green manufacturing.

Method used

Coffee grounds and polyhydroxy fatty acid esters (PHA) were introduced as composite components and modified by silane coupling agents to build a multifunctional composite system with high printing suitability and controllable degradation, enhancing interface binding and biodegradability.

Benefits of technology

It achieves a balance of high strength, toughness and controllable degradation, improves the 3D printing adaptability and biodegradation performance of materials, and meets the needs of automobiles, environmentally friendly packaging and 3D printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-strength degradable polypropylene composite material as well as a preparation method and application of the high-strength degradable polypropylene composite material. Comprising the following components in percentage by weight: 40-60% of polypropylene, 5-15% of an elastomer, 3-10% of polycaprolactone, 10-25% of coffee grounds, 5-20% of polyhydroxyalkanoate, 3-12% of calcium carbonate, 0.3-1.5% of an antioxidant and 1-3% of a silane coupling agent. According to the composite material, by introducing coffee grounds and polyhydroxyalkanoate, a multifunctional composite system with high printability and controllable degradation is constructed, so that the technical bottleneck that the mechanical property and the processing fluidity of a biomass composite material are difficult to synergistically improve is broken through; and triple balance of high toughness, low shrinkage and good printing rheological property is realized, material guarantee is provided for 3D printing products with complex structures, and the 3D printing material is suitable for the fields of automobiles, environment-friendly packaging, 3D printing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer functional materials, and relates to a polypropylene composite material, a preparation method and an application thereof, and particularly relates to a high-strength degradable polypropylene composite material, a preparation method and an application thereof. Background Art

[0002] As one of the most produced general plastics, polypropylene (PP) is widely used in automotive parts, packaging materials, daily necessities and 3D printing fields due to its excellent mechanical properties, chemical corrosion resistance and low cost. However, traditional PP materials have two core defects: firstly, their toughness is insufficient, and they are particularly prone to brittle fracture in low-temperature environments, which limits their application under complex working conditions; secondly, PP completely relies on petroleum resources and is not biodegradable, and a large number of waste PP products are disposed of by landfilling or incineration, which exacerbates resource waste and environmental pollution. In addition, in the 3D printing field, pure PP materials have a high shrinkage rate and weak interlayer bonding force, and printed parts are prone to warping and deformation. Although adding fillers (such as glass fibers, talcum powder) can improve mechanical properties, it further sacrifices the advantages of lightweight and processing fluidity, and it is difficult to meet the requirements of green manufacturing.

[0003] To balance the performance and sustainability of PP materials, in recent years, researchers have tried to achieve functional optimization through blending modification or introducing bio-based components. For example, blending elastomers (such as POE, EPDM) with PP can significantly improve toughness, but the addition of elastomers will reduce the rigidity of the material and cannot solve the biodegradation problem. Another strategy is to introduce biomass fillers (such as wood powder, bamboo fiber, coffee grounds) into PP. These fillers are derived from renewable resources, can reduce the carbon footprint of the material, and even endow partial degradation characteristics. Among them, coffee grounds, as a waste with high added value, show potential in adsorption, heat insulation and other fields due to their porous structure and high carbon content. However, the interfacial compatibility between coffee grounds and PP is extremely poor, and direct blending will lead to a sharp decline in mechanical properties (such as a reduction in tensile strength by more than 30%), and the water absorption of coffee grounds will cause problems with the dimensional stability of the material. Traditional solutions are to perform alkali treatment or acetylation modification on coffee grounds, but these methods are complex in process, high in cost, and may damage their porous structure and weaken their functionality.

[0004] Meanwhile, the rapid development of biobased degradable polymers (such as polyhydroxyalkanoates, PHA) provides new ideas for the green modification of PP. PHA is synthesized by microorganisms and can be completely degraded in the natural environment. Its mechanical properties are close to those of PP, and theoretically it can be used as an ideal blending component for PP. However, the polarity difference between PP and PHA leads to poor compatibility between the two, and simple blending is prone to phase separation, forming macroscopic defects, which instead reduces the comprehensive properties of the material. Existing studies mostly use maleic anhydride grafted PP (PP-g-MAH) as a compatibilizer, but its grafting rate is low and it may introduce toxic residues, which limits its application in the fields of food packaging or medical use. Therefore, developing a green and efficient interfacial modification strategy to achieve the multiphase compatibility of PP with PHA and biomass fillers has become the key to improving the properties of composite materials.

[0005] Although existing technologies have improved the interfacial compatibility and degradability of PP by treating biomass fillers with silane coupling agents or introducing PHA microspheres, they still face significant bottlenecks: on the one hand, traditional modification methods are difficult to balance lightweight and mechanical properties, and high-density fillers such as wood flour lead to a decrease in the specific strength of composite materials; on the other hand, the complex preparation process of PHA microspheres increases the cost, and high-content addition will seriously deteriorate the toughness of the material. In addition, although existing degradable 3D printing materials (such as PLA) have good printability, their heat resistance and toughness are poor, making it difficult to replace PP in high-temperature or high-impact environments.

[0006] Therefore, in view of the above technical problems, it is necessary to provide a high-strength degradable polypropylene composite material, which breaks through the deficiencies of polypropylene (PP)-based composite materials in biodegradability, interfacial bonding force and 3D printing performance, constructs a multifunctional composite system with high printability and controllable degradation, and makes its application range wider. Summary of the Invention

[0007] The purpose of the present invention is to provide a high-strength degradable polypropylene composite material, its preparation method and application. Aiming at the deficiencies of polypropylene (PP)-based composite materials in biodegradability, interfacial bonding force and 3D printing performance, coffee grounds and polyhydroxyalkanoates (PHA) are introduced to construct a multifunctional composite system with high printability and controllable degradation, thereby breaking through the technical bottleneck that it is difficult to synergistically improve the mechanical properties and processing fluidity of biomass composite materials, and achieving a triple balance of high toughness, low shrinkage and good print rheological properties, providing material guarantee for 3D printed products with complex structures, and being applicable to fields such as automobiles, environmental protection packaging and 3D printing.

[0008] In order to achieve the above purpose, the technical solutions provided by a specific embodiment of the present invention are as follows:

[0009] On the one hand, the present invention provides a high-strength degradable polypropylene composite material, comprising the following components in weight percentages: 40-60% of polypropylene, 5-15% of elastomer, 3-10% of polycaprolactone, 10-25% of coffee grounds, 5-20% of polyhydroxyalkanoate (PHA), 3-12% of calcium carbonate, 0.3-1.5% of antioxidant, and 1-3% of silane coupling agent.

[0010] In one or more embodiments of the present invention, the composite material comprises the following components in weight percentages: 40-45% of polypropylene, 5-15% of elastomer, 6-10% of polycaprolactone, 16-25% of coffee grounds, 10-20% of polyhydroxyalkanoate (PHA), 8-10% of calcium carbonate, 0.5-1.0% of antioxidant, and 1.5-3.0% of silane coupling agent. The composite material obtained under this ratio can achieve the coexistence of high strength and high toughness, and has higher biodegradability. At the same time, the low shrinkage rate and high melt fluidity ensure the 3D printing accuracy and processing stability; the lightweight combined with heat resistance meets the dual requirements of the automotive and packaging fields for lightweight and thermal stability of materials, making it an ideal choice for green manufacturing and functional applications.

[0011] In one or more embodiments of the present invention, the number average molecular weight (Mn) of the polyhydroxyalkanoate (PHA) is 80,000-200,000 g / mol, and the melting point is 140-180 °C.

[0012] In one or more embodiments of the present invention, the particle size range of the coffee grounds is 80-150 μm; preferably, the coffee grounds are waste coffee grounds carbonized at 200 °C for 3 hours.

[0013] In one or more embodiments of the present invention, the silane coupling agent is an epoxy-based silane coupling agent, preferably KH-560. Selecting the epoxy-based silane coupling agent can act on both coffee grounds and PHA simultaneously, reducing the risk of side reactions in the traditional multi-coupling agent compounding.

[0014] In one or more embodiments of the present invention, the polypropylene is ethylene-propylene copolymerized polypropylene or homopolymerized polypropylene, wherein the ethylene comonomer content is 5-25 wt%, preferably 10-20 wt%; the isotacticity is <90%, preferably 85-89%; the melt flow index is 15-40 g / 10 min under the conditions of 230 °C / 2.16 kg, preferably 20-35 g / 10 min; the elongation at break is ≥250%, preferably 300-500%.

[0015] In one or more embodiments of the present invention, the elastomer is ethylene-octene copolymer and / or propylene-based elastomer.

[0016] In one or more embodiments of the present invention, the polycaprolactone (PCL) is an ε-caprolactone homopolymer capped with hydroxyl groups at both ends, having a number average molecular weight of 30,000 to 80,000 g / mol and a melt index of 3 to 12 g / 10 min (80 °C / 2.16 kg).

[0017] In one or more embodiments of the present invention, the antioxidant is one or a mixture of several of hindered phenol macromolecular antioxidants, phosphite antioxidants, and alkyl ester antioxidants; preferably, the antioxidant is a combination of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010) and tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168).

[0018] In one or more embodiments of the present invention, the D50 of the calcium carbonate is 1 to 5 μm. Preferably, the calcium carbonate is activated calcium carbonate coated with stearic acid or a silane coupling agent, with a CaCO3 content ≥ 97% and a whiteness ≥ 90%.

[0019] In one or more embodiments of the present invention, the melting point of the ethylene-octene copolymer is 60 to 150 °C, preferably 65 to 100 °C; the melting point of the propylene-based elastomer is 120 to 200 °C, preferably 140 to 180 °C.

[0020] On the other hand, the present invention also provides a method for preparing the above-mentioned high-strength degradable polypropylene composite material, comprising the following steps:

[0021] 1) Take appropriate amounts of coffee grounds and polyhydroxyalkanoates, and pretreat the coffee grounds and polyhydroxyalkanoates respectively to obtain modified coffee grounds and modified polyhydroxyalkanoates;

[0022] 2) Then weigh appropriate amounts of polypropylene, elastomer, polycaprolactone, modified polyhydroxyalkanoate, and antioxidant and add them to a high-speed mixer to mix evenly to obtain a mixed material A; preferably, the high-speed mixer preferably mixes at a speed of 1000 rpm for 10 minutes;

[0023] 3) Then add appropriate amounts of dicumyl peroxide (DCP) and calcium carbonate to the high-speed mixer to mix evenly to obtain a mixed material B. The mass ratio of DCP to calcium carbonate is preferably 1:10; preferably, the high-speed mixer mixes at a speed of 3000 rpm for 10 minutes;

[0024] 4) Then sequentially put the mixed material A, the mixed material B, and the modified coffee grounds into a twin-screw extruder for melt blending and extrusion to obtain the product.

[0025] In one or more embodiments of the present invention, in step 1), the coffee grounds are modified by a method comprising the following steps: soaking the coffee grounds in dilute hydrochloric acid to remove impurities and then drying, placing the dried coffee grounds in a silane coupling agent ethanol solution and stirring for reaction, and then drying under vacuum at 80 °C until the moisture content ≤ 1%, thus obtaining the product.

[0026] In one or more embodiments of the present invention, in step 1), the polyhydroxyalkanoate is modified by a method comprising the following steps:

[0027] (1) Add the polyhydroxyalkanoate to an aqueous NaOH solution, stir at 70 °C at 200 rpm for 1 h, then neutralize with dilute hydrochloric acid, wash with deionized water, and dry at 60 °C for 6 h to obtain the dried PHA;

[0028] (2) Then crush the dried polyhydroxyalkanoate to a particle size ≤ 150 μm, dissolve the silane coupling agent in an acetic acid aqueous solution with pH = 5, mix at a ratio of polyhydroxyalkanoate: solution = 1:4, and stir for reaction at 60 °C for 2 h; then centrifuge to remove the unreacted substances, and after drying, obtain surface epoxy-functionalized, i.e., modified polyhydroxyalkanoate.

[0029] In one or more embodiments of the present invention, in step 3), the rotational speed of the twin-screw machine is 300 - 500 rpm, preferably 350 rpm; at this rotational speed of the twin-screw machine, it is ensured that the materials are fully plasticized during the extrusion process. After extrusion, cool and granulate to finally obtain a silane coupling agent-modified coffee grounds / polypropylene-PHA composite material.

[0030] Preferably, the twin-screw extruder is provided with at least two side feeding ports, and the two side feeding ports are respectively located in zone six and zone seven. Among them, mixture A is added from the main feeding port, mixture B is added from the side feeding port in zone six, and mixture C is added from the side feeding port in zone seven;

[0031] More preferably, the temperature settings of each temperature zone of the twin-screw extruder are as follows: the feeding zone (zone one) is 160 °C, the middle zone (zone two) is 170 °C, zone three is 175 °C, zone four is 180 °C, zone five is 185 °C, zone six is 190 °C, zone seven is 185 °C, zone eight is 180 °C, zone nine is 175 °C, and the head zone (zone ten) is 170 °C. In the twin-screw extrusion step, through reasonable temperature zone settings, full plasticization of the components and uniform distribution of the fillers are achieved.

[0032] On the other hand, the present invention also provides an application of the above-mentioned high-strength degradable polypropylene composite material in automotive interiors, environmentally friendly packaging, or customized 3D printing products.

[0033] Compared with the prior art, the high-strength degradable polypropylene composite material and its preparation method of the present invention address the deficiencies of polypropylene (PP)-based composite materials in biodegradability, interfacial bonding force, and 3D printing performance. Coffee grounds and polyhydroxyalkanoates (PHA) are introduced to construct a multifunctional composite system with both high printing suitability and controllable degradation. The natural porous structure of coffee grounds promotes the uniform flow of the melt in the printing nozzle through capillary action, and its surface roughness enhances the mechanical anchoring effect between the molten layers, significantly inhibiting printing warping. At the same time, PHA forms a chemical bond with the hydroxyl groups on the surface of coffee grounds through ester bonds, reducing the interfacial energy, enabling the coffee grounds to be evenly dispersed in the PP matrix, reducing the fluctuation of the flow resistance of the printing filament, and improving the extrusion stability. In addition, PHA preferentially crystallizes during the printing cooling process, fixing the porous framework of coffee grounds through a microcrystalline network to form a through-hole structure, which not only accelerates the subsequent biodegradation but also imparts the lightweight characteristics to the printed products.

[0034] By adding a silane coupling agent, the interfacial compatibility deficiencies between coffee grounds and polypropylene (PP), and between PHA and PP are simultaneously solved by synchronously modifying coffee grounds and PHA, constructing a "PP-PHA-coffee grounds" ternary synergistic system to inhibit phase separation and improve the stress transfer efficiency. This design utilizes the dual functionalization of the silane coupling agent. On the one hand, it grafts to the hydroxyl groups on the surface of coffee grounds to enhance the interfacial bonding force with PP, and on the other hand, it modifies the molecular chain of PHA to promote its compatibility with PP, thus forming a stable multiphase structure. After modification, the coffee grounds are evenly dispersed in the matrix, avoiding the deterioration of mechanical properties. PHA and PP form a microphase separation structure, and the molecular chain entanglement is enhanced through the "bridging" of silane, synergistically improving rigidity, toughness, and thermal stability. This design not only significantly improves the interfacial bonding force between coffee grounds and the polymer matrix but also effectively enhances the impact strength while maintaining the high rigidity of PP, breaking through the technical bottleneck that it is difficult to simultaneously improve the mechanical properties and processing fluidity of biomass composite materials. Thus, it breaks through the problems existing in the prior art, such as the combination of PHA and PP, which is difficult to balance lightweight and mechanical properties, the toughness of the material will be severely deteriorated when PHA is added in high content, and poor heat resistance and low toughness.

[0035] In addition, the porous characteristics of coffee grounds can adsorb degradation products to accelerate the disintegration of the material, while the microbial degradation characteristics of PHA trigger the controlled decomposition of the overall material. That is, the present invention innovatively utilizes the synergistic mechanism of the porous framework of coffee grounds and the degradation characteristics of PHA, which not only endows the printed parts with lightweight characteristics, but also regulates the melt flow behavior through capillary action, effectively improving the interlayer bonding strength and reducing the shrinkage rate of the product to less than 1.5%, thus solving the core pain point of poor adaptability of traditional PP-based materials for 3D printing. Moreover, the "adsorption-degradation" dual-trigger mechanism developed in the present invention accelerates the disintegration of the material by the porous adsorption of coffee grounds to degrade intermediate products, and combines the microbial degradation of PHA to trigger overall decomposition, resulting in a mass loss rate of 40% for the composite material under soil burial conditions in 3 months, providing an innovative solution for green manufacturing in fields such as automotive interiors.

[0036] Meanwhile, by introducing a POE elastomer and polycaprolactone (PCL) for compound toughening, on the premise of ensuring tensile strength and melt fluidity, the impact resistance and 3D printing adaptability of the material are significantly improved. This material system not only breaks through the bottleneck that it is difficult to balance the mechanical properties and processing properties of traditional biomass composites, but also realizes the degradability and functional enhancement of PP-based materials through the component synergistic effect, providing an innovative material choice for the green manufacturing of automotive interiors, environmental protection packaging, and customized 3D printed products. Through the compound toughening system of the elastomer and polycaprolactone, combined with the "molecular bridging" effect of the silane coupling agent, a triple balance of high toughness, low shrinkage, and good printing rheological properties is achieved, providing material guarantee for 3D printed products with complex structures. Detailed implementation manners

[0037] In order to enable those skilled in the art of the present technology to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present invention.

[0038] The following embodiments further illustrate the preferred specific implementation manners within the scope of the present invention. These embodiments are merely illustrative and do not limit the scope of the present invention, because many changes can be made to the present invention as long as the essence and scope are not deviated from. Detailed description of the invention

[0040] In this text, the terms "include", "comprise", "contain", "have", or other variants are intended to cover non-closed inclusion, and no distinction is made among these terms. The term "comprise" means that other steps and components can be added without affecting the final result. The term "comprise" also includes the terms "consist of" and "consist essentially of". The compositions and methods / processes of the present invention may comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.

[0041] Unless otherwise specified, the reagents and materials in this text can be obtained from conventional channels.

[0042] Formulation and usage method

[0043] Method for preparing a high-strength degradable polypropylene composite material, comprising the following steps:

[0044] (a) Soak coffee grounds in dilute hydrochloric acid with a mass fraction of 3% for 30 minutes to remove surface impurities. After washing and drying, stir and react in a silane coupling agent ethanol solution (pH = 5) for 2 hours, and then dry under vacuum at 80 °C until the moisture content ≤ 1% to obtain modified coffee grounds.

[0045] (b) Add PHA to an aqueous NaOH solution, stir at 70 °C at 200 rpm for 1 h, then neutralize with dilute hydrochloric acid, wash with deionized water, and dry at 60 °C for 6 h. Crush PHA to a particle size ≤ 150 μm, dissolve the silane coupling agent in acetic acid aqueous solution with pH = 5, mix according to PHA:solution = 1:4, and stir and react at 60 °C for 2 hours; then centrifuge to remove unreacted substances and obtain surface epoxy-functionalized PHA after drying.

[0046] (c) Add polypropylene, elastomer, polycaprolactone, modified polyhydroxyalkanoate (PHA), and antioxidant to a high-speed mixer and mix at a speed of 1000 rpm for 10 minutes to obtain mixture A.

[0047] (d) Add an appropriate amount of dicumyl peroxide (DCP) and calcium carbonate to a high-speed mixer and mix at a speed of 3000 rpm for 5 minutes to obtain mixture B.

[0048] (e) Mix material A, mix material B, and the modified coffee grounds are successively fed into a twin-screw extruder for melt blending and extrusion. The extruder should be equipped with at least two side feeding ports, and the two side feeding ports are located in zone five and zone six respectively. Among them, mix material A is added from the main feeding port, the modified coffee grounds are added from the side feeding port in zone five, and mix material B is added from the side feeding port in zone six; the temperature settings of each temperature zone of the extruder are as follows: the feeding zone (zone one) is 160 °C, the intermediate zones: zone two is 170 °C, zone three is 175 °C, zone four is 180 °C, zone five is 185 °C, zone six is 190 °C, zone seven is 185 °C, zone eight is 180 °C, zone nine is 175 °C, and the head zone (zone ten) is 170 °C. The screw speed is set at 350 rpm, and during the extrusion process, ensure that the materials are fully plasticized. After extrusion, the molten material is cooled and pelletized to finally obtain the high-strength degradable polypropylene composite material of the present invention.

[0049] Examples 1 - 5

[0050] Prepare the high-strength degradable polypropylene composite materials of Examples 1 - 5 according to the above process. The composition and content of each raw material in Examples 1 - 5 are shown in Table 1 below:

[0051] Table 1. Composition and content of each raw material in Examples 1 - 5

[0052]

[0053]

[0054] Prepare the high-strength degradable polypropylene composite materials according to the above conditions and test them. The properties of the silane coupling agent-modified coffee grounds / polypropylene-PHA composite materials obtained in Examples 1 - 5 are shown in Table 2 below, where: the density is tested according to ASTM D792 standard; the melting point is tested according to ASTM D3418 standard; the tensile strength and tensile modulus are tested according to the regulations in ASTM D638 standard, and the test speed is 50 mm / min; the notched impact strength is tested according to the regulations in ASTM D256, and the test temperature is 23 °C; the biodegradability is tested according to the regulations in ISO 14855. Under controlled composting conditions (58 °C + 2 °C, humidity 50 - 60%), the mass loss rate (%) is measured after 90 days; the melt index is tested according to ASTM D1238 standard, and the results are shown in Table 2 below;

[0055] Table 2. Properties of the high-strength degradable polypropylene composite materials obtained in Examples 1 - 5

[0056]

[0057] As can be seen from Table 2 above, the high-strength and degradable polypropylene composites obtained in Examples 1-5 exhibit excellent comprehensive properties. While maintaining high rigidity, the material also has excellent toughness, breaking through the mutually exclusive limitations of the mechanical and processing properties of traditional biomass composites. The unique "adsorption-degradation" mechanism endows it with controllable degradability, meeting the requirements of green environmental protection. The low shrinkage characteristics and stable processability significantly improve the adaptability of 3D printing and effectively inhibit warping deformation. The combination of lightweight and heat resistance shows application potential in the fields of automotive, packaging, and customized manufacturing. This system provides an innovative path for the sustainable development and functional enhancement of polypropylene materials.

[0058] As can be seen from the above experimental results, the high-strength and degradable polypropylene composites obtained with each component within the following preferred ratio ranges have relatively more excellent properties, can achieve the coexistence of high strength and high toughness, and have higher biodegradability. At the same time, the low shrinkage rate and high melt fluidity ensure the 3D printing accuracy and processing stability; the combination of lightweight and heat resistance meets the dual requirements of the automotive and packaging fields for material lightness and thermal stability, making it an ideal choice for green manufacturing and functional applications.

[0059] Propylene 40-45%, elastomer 5-15%, polycaprolactone 6-10%, coffee grounds 16-25%, polyhydroxyalkanoate (PHA) 10-20%, calcium carbonate 8-10%, antioxidant 0.5-1.0%, and silane coupling agent 1.5-3%.

[0060] Comparative Examples 1-4

[0061] Prepare high-strength and degradable polypropylene composites under the same experimental conditions as in Example 1 above, except that the composition and content of each raw material in each example are as shown in Table 3 below.

[0062] Table 3. Composition and content of each raw material in Comparative Examples 1-4

[0063]

[0064]

[0065] According to the component composition of each weight percentage in Comparative Examples 1-4, prepare silane coupling agent-modified coffee grounds / polypropylene-PHA composites according to the above preparation method, and test them by the same method as in Table 2 above. The properties of the silane coupling agent-modified coffee grounds / polypropylene-PHA composites obtained in Comparative Examples 1-4 are as shown in Table 4 below.

[0066] Table 4. Properties of the silane coupling agent-modified coffee grounds / polypropylene-PHA composites obtained in Comparative Examples 1-4

[0067]

[0068] As can be seen from Table 4 above, compared with Example 1, when both coffee grounds and PHA are missing in the formulation (Comparative Example 1), the biodegradability of the material is significantly weakened, it is more prone to warping and deformation after printing and forming, and the mechanical strength is significantly reduced, indicating that the two synergistically form a "adsorption-degradation" dynamic effect and jointly support the structural stability of the material;

[0069] If only coffee grounds are removed (Comparative Example 2), the fluidity of the material becomes poor during 3D printing and the interlayer bonding force decreases, indicating that the porous structure of coffee grounds not only accelerates degradation but also optimizes the melt flow path through capillary action and enhances the anchoring effect between printing layers; while in Comparative Example 3 without adding polyhydroxyalkanoate (PHA), the degradation rate of the material slows down and the tensile strength and impact resistance decrease simultaneously, verifying that PHA can not only serve as a "trigger point" for microbial degradation but also improve the interfacial bonding strength through improved compatibility with the matrix;

[0070] If the silane coupling agent is not added (Comparative Example 4), the mechanical properties of the material deteriorate comprehensively, the filler is unevenly dispersed during printing, and the melt fluidity fluctuates greatly, indicating that the silane coupling agent constructs a stable "bridging network" by simultaneously modifying the surfaces of coffee grounds and PHA, which not only promotes the dispersion of the two phases but also strengthens the interfacial stress transfer. Thus, the pore skeleton of coffee grounds, the degradation and compatibilization characteristics of PHA, and the interfacial synergistic effect of the silane coupling agent jointly endow the material with the integrated advantages of high mechanical strength, controllable degradability and 3D printing adaptability.

[0071] In summary, for the deficiencies of polypropylene (PP)-based composites in biodegradability, interfacial bonding force and 3D printing performance, the high-strength and degradable polypropylene composite material and its preparation method of the present invention introduce coffee grounds and polyhydroxyalkanoate (PHA) to construct a multifunctional composite system with both high printing suitability and controllable degradation. The natural porous structure of coffee grounds promotes the uniform flow of the melt in the printing nozzle through capillary action, and its surface roughness enhances the mechanical anchoring effect between the molten layers, significantly inhibiting printing warping; at the same time, PHA forms a chemical bond with the hydroxyl groups on the surface of coffee grounds through an ester bond, reducing the interfacial energy, making the coffee grounds evenly dispersed in the PP matrix, reducing the fluctuation of the flow resistance of the printing filament, and improving the extrusion stability. In addition, PHA preferentially crystallizes during printing and cooling, fixes the porous skeleton of coffee grounds through a microcrystalline network, and forms a through-hole structure, which not only accelerates the subsequent biodegradation but also endows the printed product with the characteristic of light weight.

[0072] By adding silane coupling agent and simultaneously modifying coffee grounds and PHA, the problem of insufficient interfacial compatibility between coffee grounds and polypropylene (PP), and between PHA and PP is solved simultaneously, constructing a "PP-PHA-coffee grounds" ternary synergistic system to inhibit phase separation and improve stress transfer efficiency. This design utilizes the dual functionalization of silane coupling agent. On the one hand, it grafts the hydroxyl groups on the surface of coffee grounds to enhance its interfacial binding force with PP. On the other hand, it modifies the molecular chain of PHA to promote its compatibility with PP, thus forming a stable multiphase structure. After modification, coffee grounds are uniformly dispersed in the matrix, avoiding the deterioration of mechanical properties; PHA and PP form a microphase separation structure, and the molecular chain entanglement is enhanced through the "bridging" of silane, synergistically improving rigidity, toughness and thermal stability. This design not only significantly improves the interfacial binding force between coffee grounds and polymer matrix, but also effectively improves the impact strength while maintaining the high rigidity of PP, breaking through the technical bottleneck that it is difficult to synergistically improve the mechanical properties and processing fluidity of biomass composites. Thus, it breaks through the problems existing in the prior art, such as the combination of PHA and PP, the difficulty in balancing lightweight and mechanical properties, the serious deterioration of material toughness caused by high content addition of PHA, and poor heat resistance and low toughness.

[0073] In addition, the porous characteristics of coffee grounds can adsorb degradation products to accelerate the disintegration of materials, while the microbial degradation characteristics of PHA trigger the controllable decomposition of the whole material. That is, the present invention innovatively utilizes the synergistic mechanism of the porous framework of coffee grounds and the degradation characteristics of PHA, not only endowing the printed parts with lightweight characteristics, but also regulating the melt flow behavior through capillary effect, effectively improving the interlayer bonding strength and reducing the shrinkage rate of the product to less than 1.5%, solving the core pain point of poor adaptability of traditional PP-based materials for 3D printing. And the "adsorption-degradation" dual-trigger mechanism developed in the present invention accelerates the disintegration of materials by the porous adsorption of coffee grounds to degrade intermediate products, combined with the microbial degradation of PHA to trigger overall decomposition, making the mass loss rate of the composite material reach 40% under soil burial conditions in 3 months, providing an innovative solution for green manufacturing in fields such as automotive interiors.

[0074] Meanwhile, by introducing POE elastomer and polycaprolactone (PCL) for compound toughening, on the premise of ensuring tensile strength and melt fluidity, the impact resistance and 3D printing adaptability of the material are significantly improved. This material system not only breaks through the bottleneck that it is difficult to balance the mechanical properties and processing properties of traditional biomass composites, but also realizes the degradability and functional enhancement of PP-based materials through the component synergistic effect, providing an innovative material choice for the green manufacturing of automotive interiors, environmental protection packaging and customized 3D printed products. Through the compound toughening system of elastomer and polycaprolactone, combined with the "molecular bridging" effect of silane coupling agent, the triple balance of high toughness, low shrinkage and good printing rheological properties is achieved, providing material guarantee for 3D printed products with complex structures.

[0075] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above-described exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, in any regard, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be embraced within the present invention.

[0076] In addition, it should be understood that although this specification is described according to embodiments, not every embodiment only contains an independent technical solution. This narrative manner of the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A high-strength degradable polypropylene composite material, comprising the following components in weight percentages: 40-60% of polypropylene, 5-15% of elastomer, 3-10% of polycaprolactone, 10-25% of coffee grounds, 5-20% of polyhydroxyalkanoate, 3-12% of calcium carbonate, 0.3-1.5% of antioxidant, and 1-3% of silane coupling agent.

2. The high-strength degradable polypropylene composite material according to claim 1, wherein The composite material comprises the following components in weight percentages: 40-45% of polypropylene, 5-15% of elastomer, 6-10% of polycaprolactone, 16-25% of coffee grounds, 10-20% of polyhydroxyalkanoate, 8-10% of calcium carbonate, 0.5-1.0% of antioxidant, and 1.5-3.0% of silane coupling agent.

3. The high-strength degradable polypropylene composite material according to claim 1 or 2, characterized in that, The number-average molecular weight of the polyhydroxyalkanoate is 80,000-200,000 g / mol, and the melting point is 140-180 °C.

4. The high-strength degradable polypropylene composite material according to any one of claims 1 to 3, characterized in that, The particle size range of the coffee grounds is 80-150 μm; preferably, the coffee grounds are waste coffee grounds carbonized at 200 °C for 3 hours; or The silane coupling agent is an epoxy-based silane coupling agent.

5. The high-strength degradable polypropylene composite material according to any one of claims 1 to 4, characterized in that The polypropylene is ethylene-propylene copolymerized polypropylene or homopolymerized polypropylene, wherein the ethylene comonomer content is 5-25 wt%, preferably 10-20 wt%; the isotacticity is <90%, preferably 85-89%; the melt flow index is 15-40 g / 10 min under the conditions of 230 °C / 2.16 kg, preferably 20-35 g / 10 min; the elongation at break is ≥250%, preferably 300-500%; or The elastomer is ethylene-octene copolymer and / or propylene-based elastomer; or The polycaprolactone (PCL) is an ε-caprolactone homopolymer capped with hydroxyl groups at both ends, with a number-average molecular weight of 30,000-80,000 g / mol and a melt index of 3-12 g / 10 min (80 °C / 2.16 kg); or The antioxidant is one or a mixture of several of hindered phenol macromolecular antioxidants, phosphite antioxidants, and alkyl ester antioxidants; preferably, the antioxidant is a combination of pentaerythritol tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris [2,4-di-tert-butylphenyl] phosphite; or The D50 of the calcium carbonate is 1-5 μm. Preferably, the calcium carbonate is active calcium carbonate coated with stearic acid or silane coupling agent, with a CaCO3 content of ≥97% and a whiteness of ≥90%.

6. The high-strength degradable polypropylene composite material according to claim 5, wherein The melting point of the ethylene-octene copolymer is 60-150 °C, preferably 65-100 °C; the melting point of the propylene-based elastomer is 120-200 °C, preferably 140-180 °C.

7. The preparation method of the high-strength degradable polypropylene composite material according to any one of claims 1 to 6, comprising the following steps: 1) Take appropriate amounts of coffee grounds and polyhydroxyalkanoate, and pretreat the coffee grounds and polyhydroxyalkanoate respectively to obtain modified coffee grounds and modified polyhydroxyalkanoate; 2) Weigh an appropriate amount of polypropylene, elastomer, polycaprolactone, modified polyhydroxyalkanoate, and antioxidant, and add them to a high-speed mixer to mix evenly to obtain mixture A. Preferably, the high-speed mixer preferably mixes at a speed of 1000 rpm for 10 minutes. 3) Then, add an appropriate amount of dicumyl peroxide (DCP) and calcium carbonate to the high-speed mixer to mix evenly to obtain mixture B. The mass ratio of DCP to calcium carbonate is preferably 1:

10. Preferably, the high-speed mixer mixes at a speed of 3000 rpm for 10 minutes. 4) Then, successively feed mixture A, mixture B, and modified coffee grounds into a twin-screw extruder for melt blending and extrusion to obtain the product.

8. The preparation method of the high-strength degradable polypropylene composite material according to claim 7, characterized in that, In step 1), the coffee grounds are modified by a method including the following steps: soak the coffee grounds in dilute hydrochloric acid to remove impurities and dry them, then place the dried coffee grounds in a silane coupling agent ethanol solution and stir to react, and then dry them under vacuum at 80 °C until the moisture content ≤ 1%, thus obtaining the modified coffee grounds; or The polyhydroxyalkanoate is modified by a method including the following steps: (1) Add the polyhydroxyalkanoate to an aqueous NaOH solution, stir at 70 °C at 200 rpm for 1 h, then neutralize with dilute hydrochloric acid, wash with deionized water, and dry at 60 °C for 6 h to obtain the dried PHA. (2) Then, crush the dried polyhydroxyalkanoate to a particle size ≤ 150 μm, then dissolve the silane coupling agent in an acetic acid aqueous solution with pH = 5, mix at a ratio of polyhydroxyalkanoate: solution = 1:4, and stir to react at 60 °C for 2 hours; then centrifuge to remove unreacted substances, and after drying, obtain surface epoxy-functionalized, that is, modified polyhydroxyalkanoate.

9. The preparation method of the high-strength degradable polypropylene composite material according to claim 7, characterized in that, In step 3), the rotational speed of the twin-screw machine is 300 - 500 rpm, preferably 350 rpm. Preferably, the twin-screw extruder is configured with at least two side feeding ports, and the two side feeding ports are respectively located in zone six and zone seven. Among them, mixture A is added from the main feeding port, mixture B is added from the side feeding port in zone six, and mixture C is added from the side feeding port in zone seven. More preferably, the temperature settings of each temperature zone of the twin-screw extruder are as follows: the feeding zone (zone one) is 160 °C, the middle zone (zone two) is 170 °C, zone three is 175 °C, zone four is 180 °C, zone five is 185 °C, zone six is 190 °C, zone seven is 185 °C, zone eight is 180 °C, zone nine is 175 °C, and the head zone (zone ten) is 170 °C.

10. The application of the high-strength degradable polypropylene composite material according to any one of claims 1 to 6 in automotive interiors, environmentally friendly packaging, or customized 3D printing products.

Citation Information

Cited By

  • High-strength material prepared from recycled PP

    CN120699357A